Preparação de derivados do ácido caféico e avaliação das suas atividades antimicrobianas - Araújo, Marianna Oliveira de (2017)
The present dissertation show the results obtained from the study of a collection of structurally related caffeic acid derived and their antimicrobial evaluation. Increased microbial resistance to drugs, causing thousands of deaths per year, mainly in immunocompromised individuals, motivated the development of the present study. Esters derived from caffeic acid have a large spectrum of pharmacological activities, including antimicrobial activity. Therefore, the objective of this work was to evaluate the antimicrobial activity of sixteen esters derived from coffeic acid on different species of Staphylococcus, Eschericia and Candida. Alkyl and aryl esters derived from caffeic acid were prepared by Fischer esterification, reaction with alkyl and aryl halides, and Mitsunobu reaction. In the characterization of the products were used infrared spectroscopic methods, 1H and 13C nuclear magnetic resonance, as well as high resolution mass spectrometry for the inedited derivatives. All the esters were submitted to antimicrobial tests by broth microdilution, with chloramphenyl and nystatin as antimicrobial control. 16 esters of caffeic acid were obtained in yields varying from 11.82-93.06%, 6 were inedited in the literature. Six esters presented antifungal activity, while all compounds were bioactive in the test of antibacterial activity. Thus, esters ME7 and ME13 demonstrated the best antifungal activities (128 and 256 μg / mL, respectively). While in the antibacterial tests, the results were more sensitive to the Gram negative strain (50 to 400 μg / mL), with better results for the alkyl esters ME3, ME6 and ME7, and for the aryl ME10, ME13, ME14 and ME16. These results show that middle chain alkyl substituents and certain aryl groups potentiate antimicrobial activity.